Conflict of Traditional and Modern Transportation at the Pier (Study on Karang Baru Village, Sumber Marga Telang District, Banyuasin Regency) - Sari Salsabila; Ryllian Chandra Eka Viana; Reni Apriani (Universitas Muhammadiyah Palu, 2026)
This study analyzes the conflict between traditional transportation and modern transportation operating at the Karang Baru Village Pier, Sumber Marga Telang District, Banyuasin Regency. The emergence of modern transportation with a more structured and efficient service system creates tension for traditional transportation actors who feel that there is a threat to the sustainability of their livelihoods. The conflicts that arise are not only related to aspects of operating space competition and tariff differences, but also concern changes in social interaction patterns and local economic structures. This study aims to identify the forms of conflict that occur and analyze the factors behind the emergence of these conflicts in the context of transportation service transformation. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews with traditional and modern transportation drivers, service users, village officials, and parties who have an interest in transportation management in the area. The results of the study show that the conflicts that occur can be explained through the Theory of Functional Conflict, where conflict is seen as a social mechanism that arises due to an imbalance of interests resulting in unequal access to passengers, changes in service structure, and the absence of regulations that are able to accommodate the interests of both parties. In addition, the economic condition of the community and dependence on the transportation sector reinforce the intensity of the prolonged conflict.